Contributing but Unrecognised: Gender Dynamics in Natural Resource Management among Women Farmers in Kubu Raya - Amira Fazilah; Mentari; Nurul Fadilah (Journal of Creative Power and Ambition (JCPA), 2026)
Natural resources are the primary livelihood base for farming communities in rural areas, and their management involves both men and women. This study examines the gender-based division of labour in natural resource management within farming communities in Sungai Raya Sub-district, Kubu Raya Regency, focusing on the agricultural and fisheries sectors. It aims to analyse women’s roles, identify the barriers they face in accessing and controlling resources, and evaluate how gender roles affect resource control and family welfare. Using a qualitative approach, data were collected through in-depth interviews, focus group discussions, participatory observation, and documentation involving male and female farmers, community leaders, and local officials, then analysed thematically. The findings reveal significant gender disparities: women are heavily involved in domestic tasks such as crop maintenance and food processing, yet are largely excluded from strategic decisions on the allocation and use of natural resources. This inequality is reinforced by prevailing social and cultural norms and constrains both family welfare and the sustainability of resource management. The study underlines the need for gender-responsive empowerment through access to training, technology, financial resources, and participation in decision-making and more inclusive policies to achieve fair and sustainable natural resource management